2023
DOI: 10.1021/acs.analchem.2c04608
|View full text |Cite
|
Sign up to set email alerts
|

Light-Amplified CISS-Based Hybrid QD-DNA Impedimetric Device for DNA Hybridization Detection

Abstract: We design and build a novel light-amplified electrochemical impedimetric device based on the CISS effect to detect DNA hybridization using a hybrid quantum dot (QD)-DNA monolayer on a ferromagnetic (FM) Ni/Au thin film for the first time. Using spin as a detection tool, the current research considers the chiral-induced spin selectivity (CISS) phenomenon. After injecting a spin current into the QD-DNA system with opposite polarities (up and down), the impedimetric device revealed a large differential change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The spin-specific change in charge transport through chiral molecules in electrochemical tunnel junctions, be that through monitoring changes in current or charge transfer rate, likely arise from the same phenomenon: spin-dependent changes in resistance for charge transport. This supposition is supported by recent impedance measurements made on DNA coated ferromagnetic electrodes, in which an equivalent circuit model analysis is used to extract the charge transfer resistance as a function of applied magnetic field. For the DNA assemblies, deviations in charge transfer resistance with magnetization orientation are observed, owing to the CISS effect; however, in achiral systems the charge transfer resistance is unaffected by the magnetic field orientation.…”
Section: Methods For Measuring Cissmentioning
confidence: 88%
See 2 more Smart Citations
“…The spin-specific change in charge transport through chiral molecules in electrochemical tunnel junctions, be that through monitoring changes in current or charge transfer rate, likely arise from the same phenomenon: spin-dependent changes in resistance for charge transport. This supposition is supported by recent impedance measurements made on DNA coated ferromagnetic electrodes, in which an equivalent circuit model analysis is used to extract the charge transfer resistance as a function of applied magnetic field. For the DNA assemblies, deviations in charge transfer resistance with magnetization orientation are observed, owing to the CISS effect; however, in achiral systems the charge transfer resistance is unaffected by the magnetic field orientation.…”
Section: Methods For Measuring Cissmentioning
confidence: 88%
“…DNA (see refs , , , , , , , ) and α-helical oligopeptides (see refs , , , , , , , , , , , , , , , , , ) have been widely used to explore the CISS effect and its connection with molecular properties. Having been investigated by spin-dependent photoemission, transport, electrochemical, and spin-dependent polarization experiments, they comprise testbed systems for comparisons between methods.…”
Section: Materials and Molecules Exhibiting Cissmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been demonstrated by several different methods, including electrochemical, Mott polarimeter, conductive atomic force microscopy, etc. The CISS effect describes the spin-filtering ability of chiral molecules made up of C, N, or O, despite their very low spin–orbit coupling (∼3 meV) constants compared to 3d-group ferromagnetic materials such as Fe, Co, or Ni (∼800 meV). The phenomenon of spin-filtering has been reported for a range of molecular structures, including amino acids, peptides, polymers, proteins, and dsDNA. , Among these, the spin filtering efficacy of dsDNA has been shown to reach noteworthy levels, as high as 60%, despite the fact that the inherent spin–orbit coupling constant of dsDNA is quite low, theoretically estimated to be around 10 meV. , The CISS phenomenon exhibits a wide range of applications, encompassing several fields such as molecular spintronics, water splitting, and DNA biosensing. In DNA biosensors, the detection of DNA hybridization plays a pivotal role that finds applications in genomics, drug discovery, diagnosis of hereditary diseases, detection of infectious agents, and the discovery of gene-targeted drugs . In our recently published work, we investigated sequence-specific spin selectivity through several dsDNA using time-correlated single-photon counting (TCSPC) measurements .…”
mentioning
confidence: 99%
“…5,6 Prashant et al designed a light-amplified EC impedimetric device based on a hybrid quantum dot (QD)-DNA structure yielding 7% more spinpolarized electrons under light, which offered an enlarged variation in the charge-transfer resistance (DR ct ). 7 Wang et al found that the current response of ascorbic acid (AA) increases by 1.3fold due to hot electron effective transport of plasmonic gold nanostars (AuNSs). 8 The construction of photoactive nanostructures with high carrier concentration and specific electron transport is crucial for amplifying EC signals.…”
mentioning
confidence: 99%